NILAI-NILAI SOSIAL DAN MORAL DALAM NOVEL “AYAHKU BUKAN PEMBOHONG” KARYA TERE LIYE - Wulandari, Diana; Wardarita, Ratu; Rukiyah, Siti (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
This research aims to describe the social and moral values ​​contained in the novel My Father is Not a Liar by Tere Liye. The method used is a descriptive qualitative method, with data collection techniques in this research using documentation techniques, the data used in this research are stories contained in the Social Values ​​and Morals in the novel Ayahku Bukan Liar by Tere Liye. Contains social and moral values. Social values, namely: social values ​​related to caring attitudes. Caring about other people by providing help to people in need, giving a friendly attitude to others, and caring about the environment by loving and protecting nature reflects an individual who has good social relations. Meanwhile, moral values ​​are: always being grateful and having an open and clean heart. Tell the truth and be disciplined in your time and obey the rules. Have curiosity about new things. Feel happy in the family with a simple life. Be patient in facing injustice. Have harmonious relationships in the family.